Housing for the Elderly: Addressing Gaps in Knowledge Through the Lens of Age-Friendly Communities. Issue 2 (3rd April 2017) - Frochen, Stephen; Pynoos, Jon
ABSTRACT: We identify salient research gaps in the elderly housing research and respond to the lack of knowledge, guided by Menec, Means, Keating, Parkhurst, and Eales' (2011 ) age-friendly communities framework. These gaps in knowledge include age-friendliness, aging in place, conceptualization of home, falls, housing as it relates to disability and health, person-environment fit, and housing programs and initiatives. We discuss how the age-friendly paradigm can inform these areas of the literature and address problems presented in each. This review is intended to provide a roadmap for future researchers, administrators, clinicians, and policy makers.